Effects of Chlorpyrifos Exposure on Proliferation and Differentiation in Human Neural Progenitor Cells - Kim, Hee Yeon (My University, 2013)
An in vitro human neural progenitor cell (hNPCs) model was established to study adverse effects of the organophosphate pesticide chlorpyrifos (CP) during neuronal proliferation and differentiation. CP is of interest given its association with altered neurodevelopment in children. Commercially available hNPC ENStem-ATM cells (Millipore) were expanded in serum free proliferation expansion medium (PEM) and differentiated in HyClone neural differentiation medium (HDM). Cells were pre incubated with PEM overnight, then incubated for 72 hours in either PEM or HDM with CP (0-200 ìg/mL). Dose-dependent decreases in cell viability were observed in cells cultured in PEM and HDM, with significantly greater effects of CP on cells in the HDM (78%±3.2%) than in the PEM (84%± 3.6%) at concentrations of CP 20 ìg/mL. Cells grown under differentiating conditions were more sensitive to CP. Long-term cultures of hNPCs had significantly increased expression of neuronal structure markers (â-tubulin III, MAP2) as well as in neuronal functional marker (á-synuclein) over time under differentiating culture conditions. Simultaneously, proliferation marker (PCNA) expression decreased over time in long term differentiating conditions. Under proliferation cell culture conditions, there were no significant changes in expression of these neuronal markers. hNPCs were treated with CP (0-20 ìg/mL) under both proliferation and differentiation cell culture conditions and the effects on these neuronal stage markers were observed at 72 hrs. CP had a dose-dependent effect on expression of â-tubulin III, MAP2, and PCNA though there were no differential effects between the responses to CP under proliferation and differentiation culture conditions. These results suggest that, while proliferating and differentiating hNPCs have different sensitivity to CP, common pathways of response are affected within both conditions. Alterations of neuronal protein markers during proliferation and differentiation by CP treatment indicate cell stage-specific molecular and cellular response outcome pathways and provide mechanistic clues for understanding the potential effects of environmental agents on different processes during neurodevelopment.
Thesis (Master's)--University of Washington, 2013
Keywords: Chlorpyrifos; Differentiation; Human Neural Progenitor Cells; Organophosphate Pesticide; Proliferation; Toxicology; environmental health